Critical Thinking and Metacognition: Processes and Outcomes within the Learning Cycles - Margaret Anna McMillan; Penelope Jane Little; Susie Yoon; Meeyoung Park (Halla Newcastle Education and Research Center, 2022)
Over the last two decades policy developers across the world have set directions for educational change in pursuit of graduate outcomes that better prepare professionals for the future. Suggestions for radical change in educational practices has meant a need to revisit curricula to question the extent to which graduate outcomes are consistent with contemporary population and workplace needs. Discussion has centred on more process-oriented educational design that aims for learning outcomes especially those acknowledging a need for critical thinking and metacognition as a graduate outcome for professionals. A contextual appraisal of contemporary workplaces i) reveals a need for changes in systems and processes and ii) suggests a need for change in professional practices that in turn impact on educational preparation for practice eg i) movement towards student-centered educational design and ii) encouraging values consistent with ongoing learning in dynamic workplaces. It is the authors' opinion that educators are at risk of minimising learning processes that lead to critical thinking and metacognition. We suggest that where processes are introduced in learning events, assessment/evaluation tasks have not provided evidence of outcomes consistent with curriculum aims. In the future, curriculum renewal should include interrogation of appropriate assessment tasks that provide evidence of outcomes that reflect ability to think critically and reflect on processes in a manner consistent with metacognition. Research that focusses on the nature and extent of those outcomes is also warranted.